Ultrahigh rate capabilities of lithium-ion batteries from 3D ordered hierarchically porous electrodes with entrapped active nanoparticles configuration - Huang, Xin (2014)
Three dimensional (3D) ordered hierarchically porous electrodes with an entrapped active nanoparticles configuration afford an extremely effective conductive 3D network from the micrometer to the nano meter scale for fast electron and Li-ion transport, and also allow the development of a stable solid electrolyte interphase over the electrode materials, therefore exhibiting extraordinary rate capabilities.